Service Quality and Customer Loyalty: The Mediating Role of Customer Satisfaction and Perceived Value in Investment Platforms - Theodore, Nathanael Felix; Rodhiah (Yayasan Gema Bina Nusantara, 2026)
This study examines how service quality impacts customer loyalty among users of the XYZ investment application in Indonesia. Customer satisfaction and perceived value are the mediating variables. The study employs a quantitative, descriptive, cross-sectional design. The sample consists of 204 active XYZ application users who were selected through purposive sampling. Data were obtained via structured online questionnaires and analyzed using partial least squares–structural equation modeling (PLS-SEM) with SmartPLS version 4. The results reveal the following: Service quality positively and significantly affects customer loyalty; service quality positively and significantly influences customer satisfaction; service quality significantly enhances perceived value; customer satisfaction significantly affects customer loyalty; perceived value significantly influences customer loyalty; customer satisfaction partially mediates the relationship between service quality and customer loyalty; and perceived value likewise partially mediates the effect of service quality on customer loyalty. These findings suggest that improving service performance can increase perceived value and customer satisfaction, thereby strengthening user loyalty toward digital investment platforms.